2007
DOI: 10.1021/bi602354t
|View full text |Cite
|
Sign up to set email alerts
|

The Carboxy-Terminal Region of apoA-I Is Required for the ABCA1-Dependent Formation of α-HDL But Not Preβ-HDL Particles in Vivo

Abstract: ABCA1-mediated lipid efflux to lipid poor apoA-I results in the gradual lipidation of apoA-I. This leads to the formation of discoidal HDL which are subsequently converted to spherical HDL by the action of LCAT. We have investigated the effect of point mutations and deletions in the carboxyterminal region of apoA-I on the biogenesis of HDL using adenovirus-mediated gene transfer in apoA-I deficient mice. It was found that the plasma HDL levels were greatly reduced in mice expressing the carboxy-terminal deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…The mutant apoA-I ⌬61-78, and ⌬1-59 ⌬185-243 forms were produced using baculovirus expression system (22). Adenoviruses expressing ⌬185-243 and ⌬220 -243 were generated as described previously (23,24). The adenoviruses expressing L218A/L219A/V221A/L222A and E223A/K226A were generated in a similar way (25).…”
Section: Methodsmentioning
confidence: 99%
“…The mutant apoA-I ⌬61-78, and ⌬1-59 ⌬185-243 forms were produced using baculovirus expression system (22). Adenoviruses expressing ⌬185-243 and ⌬220 -243 were generated as described previously (23,24). The adenoviruses expressing L218A/L219A/V221A/L222A and E223A/K226A were generated in a similar way (25).…”
Section: Methodsmentioning
confidence: 99%
“…These data indicated that in apoA-I Ϫ / Ϫ × apoE Ϫ / Ϫ mice, the apoA-I[218-222] mutant caused a defective lipidation of apoA-I, possibly due to defective apoA-I/ABCA1 interaction, which resulted in the generation of only pre-␤ -HDL particles that could not be converted to mature ␣ -HDL particles. Previous studies showed that C-terminal deletion mutants that remove the 220-231 region of apoA-I prevented the biogenesis of normal ␣ -HDL particles but allowed the formation of pre-␤ -HDL particles ( 1,15 ). Similar pre-␤ -HDL particles have been found in the plasma of ABCA1-defi cient mice and humans carrying ABCA1 mutations that are characterized by HDL defi ciency (36)(37)(38).…”
Section: Rationale For Selection Of the Mutationsmentioning
confidence: 77%
“…The two studies enhance our understanding of the complex factors that contribute to the correct extracellular assembly, maturation, and proteomic composition of HDL. Future studies are required to identify by existing and new assays how the aberrant forms of HDL identifi ed in these and previous studies ( 1,2,10,11,15,18,19 ) Supplemental Material can be found at:…”
Section: Lcat Corrects the Aberrant Hdl Phenotype Caused By The Apoa-mentioning
confidence: 99%